1995
DOI: 10.1083/jcb.131.6.1609
|View full text |Cite
|
Sign up to set email alerts
|

alpha-2 Macroglobulin receptor/Ldl receptor-related protein(Lrp)-dependent internalization of the urokinase receptor.

Abstract: Abstract. The GPI-anchored urokinase plasminogen activator receptor (uPAR) does not internalize free urokinase (uPA). On the contrary, uPAR-bound complexes of uPA with its serpin inhibitors PAI-1 (plasminogen activator inhibitor type-l) or PN-1 (protease nexin-1) are readily internalized in several cell types. Here we address the question whether uPAR is internalized as well upon binding of uPA-serpin complexes. Both LB6 clone 19 cells, a mouse cell line transfected with the human uPAR cDNA, and the human U937… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
183
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(192 citation statements)
references
References 64 publications
8
183
1
Order By: Relevance
“…The MEF-2 cultures accumulated increased amounts of uPA in the medium, and the cells expressed increased amounts of cell-surface uPAR. These findings are consistent with previous studies demonstrating binding of free uPA (not uPAR-associated) to LRP (30,32) and endocytosis of uPAR in complex with LRP under certain conditions (35).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The MEF-2 cultures accumulated increased amounts of uPA in the medium, and the cells expressed increased amounts of cell-surface uPAR. These findings are consistent with previous studies demonstrating binding of free uPA (not uPAR-associated) to LRP (30,32) and endocytosis of uPAR in complex with LRP under certain conditions (35).…”
Section: Discussionsupporting
confidence: 93%
“…Expression of increased amounts of cell-surface uPAR by MEF-2 cells is consistent with the studies of Conese et al (35), which demonstrated a role for LRP in mediating the internalization of cell-surface uPAR. We hypothesized that LRP deficiency, in the MEF-2 cells, allowed these cells to establish a higher equilibrium level of cell-surface uPAR.…”
Section: Figsupporting
confidence: 90%
See 1 more Smart Citation
“…However, the study demonstrated that PrP C followed a different endocytic route than other GPIanchored proteins, such as CD59, which showed no enrichment in caveolae (Peters et al, 2003). Other instances of such protein-specific modulation are binding of a complex of the urokinase-type plasminogen activator (uPA) and its GPIanchored uPA receptor to the ␣-2 macroglobulin receptor/ low-density lipoprotein receptor-related protein (Nykjaer et al, 1992;Conese et al, 1995); and GPI-anchored CD14, which interacts with bacterial lipopolysaccharide (LPS) bound to the plasma-LPS-binding protein (Poussin et al, 1998;Triantafilou et al, 2001). In the absence of lateral associations of the type described above, or cross-linking and internalization through the caveolar/raft-dependent pathway (Nabi and Le, 2003), GPI-anchored proteins seem to be selectively internalized through a dynamin-independent pathway (Fivaz et al, 2002;Sabharanjak et al, 2002;Guha et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The process of plasminogen activation in a healthy organism is controlled through the availability of PAs, localized activation, and interaction with specific inhibitors (PAIs). At the cell surface, urokinase-type plasminogen activator (uPA) binds to its specific receptor (urokinasetype plasminogen activator receptor (uPAR)), then binds its inhibitor plasminogen activator inhibitor-1 (PAI-1), localized in the matrix, and the complex is internalized by endocytic receptors such as the low-density lipoprotein receptor-related protein (LRP) [Orth et al, 1994;Conese et al, 1995]. Recent evidence suggests that the uPA/uPAR system plays a role in the regulation of cell-matrix interactions such as cell adhesion and migration [Irigoyen et al, 1999].…”
mentioning
confidence: 99%